PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DESA MARIO - Hikma, Nurul; Sellang, Kamaruddin; Useng, Abd Razak; Sani, Yasir (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to examine the utilization of information technology on the quality of public services and the factors that influence the utilization of information technology on the quality of public services at the Mario Village Office. The type of research used in this study is a quantitative approach. The sample of this study was 37 people. The sampling method used saturated samples. The data collection technique used in this study was a questionnaire. Data analysis was carried out using simple linear regression analysis with the help of SPSS version 22.0 for windows. Based on the results of the simple null regression test, the significance value is 0.003 <0.05 and the calculated t value is 3.143> t table 1.689, which means that there is an influence. The use of information technology has an influence of 57,2 % on the quality of public services at the Mario Village Office, while the remaining 42,8 % is influenced by other variables that were not studied. Factors that influence the quality of public services at the Mario Village Office are Social Factors, Affect, Complexity, Task Suitability, Long-Term Consequences, Facilitating Conditions. So, the value of the factors that influence the quality of public services at the Mario Village Office is 80% of the 100% expected results.